ANALISIS KESULITAN SISWA DALAM MEMAHAMI BACAAN BAHASA INGGRIS - Maryatun, Maryatun; Ismu Purwaningsih, Dewi; Yolanda, Alvina (Pengelola Jurnal Politeknik Negeri Ketapang, 2024)
This research aims to find out how difficult reading is for class IX students and what efforts the teacher made to overcome them Difficulty of reading in class IX junior high school students at the Darudda’wah Islamic boarding school in Punggur Kecil. Type of research Used in research is to use a qualitative approach case study. The subjects in this research were class IX students and teachers in class IX junior high school at the small Punggur Darudda’wah Islamic boarding school. Data collection techniques use questionnaires and interviews. The collection instruments in this research are questionnaires and interviews. The research results show that many students experience this difficulty reading. The types of difficulties experienced by students, namely, participants Students have difficulty recognizing and understanding letters, lack of memory, difficulty pronouncing English reading, laziness during English lessons, often forgetting the meaning of English reading, not reading English properly, not enjoying English lessons. Efforts made by teachers to overcome the reading difficulties of class IX students at the Darudda’wah Islamic boarding school in Punggur Kecil is by using interesting and effective learning media, Increasing self-confidence and providing motivation, and never blaming the conditions experienced by students, and providing programs Remedial reading to class IX students at the Darudda’wah Islamic boarding school in Punggur Kecil.